Incidence and Long‐Term Outcomes of Stroke in Patients Presenting With ST‐Segment Elevation–Myocardial Infarction: Insights From the Midwest STEMI Consortium - Michael Megaly; Mehmet Yildiz; Edward Tannenbaum; Brynn Okeson; Marshall W. Dworak; Ross Garberich; Scott Sharkey; Frank Aguirre; Mark Tannenbaum; Timothy D. Smith; Timothy D. Henry; Santiago Garcia (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Contemporary real‐world data on stroke in patients presenting with ST‐segment–elevation myocardial infarction (STEMI) are scarce. Methods and Results We evaluated the incidence, trends, cause, and predictors of stroke from 2003 to 2019 in 4 large regional STEMI programs in the upper Midwest that use similar transfer and treatment protocols. We also evaluated the long‐term impact of stroke on 5‐year mortality. Multivariate logistic and Cox regression analysis was used to identify variables independently associated with stroke in patients presenting with STEMI and identify variables associated with 5‐year mortality. A total of 12 868 patients presented with STEMI during the study period. Stroke occurred in 98 patients (0.76%). The incidence of stroke remained stable over time (0.5% in 2003, 1.2% in 2019; P‐trend=0.22). Most (75%) of strokes were ischemic, with a median time to stroke symptoms of 14 hours after primary percutaneous coronary intervention (interquartile range, 4–72 hours), which led to a small minority (3%) receiving endovascular treatment and high in‐hospital mortality (18%). On multivariate regression analysis, age (increment of 10 years) (odds ratio [OR], 1.32; 95% CI, 1.10–1.58; P‐value=0.003) and preintervention cardiogenic shock (OR, 2.03; (95% CI, 1.03–3.78; P=0.032)) were associated with a higher risk of in‐hospital stroke. In‐hospital stroke was independently associated with increased risk of 5‐year mortality (hazard ratio, 2.01; 95% CI, 1.13–3.57; P=0.02). Conclusions In patients presenting with STEMI, the risk of stroke is low (0.76%). A stroke in patients presenting with STEMI is associated with significantly higher in‐hospital (18%) and long‐term mortality (35% at 5 years). Stroke was associated with double the risk of 5‐year death.